2013
DOI: 10.1016/j.ejphar.2013.04.017
|View full text |Cite
|
Sign up to set email alerts
|

Diminazene aceturate improves autonomic modulation in pulmonary hypertension

Abstract: We have previously demonstrated that diminazene aceturate (DIZE), a putative angiotensin 1–7 converting enzyme activator, protects rats from monocrotaline (MCT)-induced pulmonary hypertension (PH). The present study was conducted to determine if the beneficial effects of DIZE are associated with improvements in autonomic nervous system (ANS) modulation. PH was induced in male rats by a single subcutaneous injection of MCT (50mg/kg). A subset of MCT rats were treated with DIZE (15mg/kg/day) for a period of 21 d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
33
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(36 citation statements)
references
References 37 publications
3
33
0
Order By: Relevance
“…Furthermore, frequency-domain measurements (HF, LF, and TP) were all decreased compared to those in control patients. Our study findings were consistent with those of previous reports showing that HRV measurements were decreased in animal models 27,28 and clinical subjects 11,29,30 with PAH. Since RMSSD is used to evaluate short-term heart rate variation modulated by parasympathetic activity, it is possible that the parasympathetic modulation activity was impaired, leading to a reduced RMSSD in patients with IPAH.…”
Section: Autonomic Nervous System Function and Hrv In Ipah Patientssupporting
confidence: 95%
See 1 more Smart Citation
“…Furthermore, frequency-domain measurements (HF, LF, and TP) were all decreased compared to those in control patients. Our study findings were consistent with those of previous reports showing that HRV measurements were decreased in animal models 27,28 and clinical subjects 11,29,30 with PAH. Since RMSSD is used to evaluate short-term heart rate variation modulated by parasympathetic activity, it is possible that the parasympathetic modulation activity was impaired, leading to a reduced RMSSD in patients with IPAH.…”
Section: Autonomic Nervous System Function and Hrv In Ipah Patientssupporting
confidence: 95%
“…3 Recently, some animal studies showed that interventions that improve HRV might also reduce the risk of sudden cardiac death. 27,28,40 Further understanding of the causality and mechanisms between low HRV and mortality will be useful in developing treatments that could increase HRV and hopefully improve survival. The current study might be helpful in delineating the supplemental prognostic information contained in HRV and provide a research guide for prospective studies in future.…”
Section: Clinical Implicationmentioning
confidence: 99%
“…However, despite of its impressive antihypertensive and cardiovascular protective effects, there are very few follow-up studies to confirm these findings by this and other groups. Additionally, a chemical compound, diminazene aceturate (DIZE), has been promoted as a potential ACE2 activator to treat ischemia-induced cardiac pathophysiology, pulmonary hypertension, and ischemic stroke [160163]. DIZE is a widely used antiprotozoal agent to treat trypanosomiasis in domestic livestock, but rarely used in humans [164].…”
Section: New Insights Into the Roles And Therapeutic Implications mentioning
confidence: 99%
“…This was interpreted as that DIZE may have cerebroprotective properties against endothelin 1-induced ischemic stroke [162]. Subsequent studies by the same group of investigators have demonstrated that DIZE significantly protected rats from monocrotaline (MCT)-induced pulmonary hypertension (PH) [163,165], and decreased myocardial infarction (MI)-induced infarct area, LV remodeling post-MI, and restored normal balance of the cardiac renin-angiotensin system [160]. Recently, the cardiovascular, hypertensive, and renal effects of targeting ACE2 with DIZE in various animal models have been comprehensively reviewed elsewhere often with mixed or conflicting results [161].…”
Section: New Insights Into the Roles And Therapeutic Implications mentioning
confidence: 99%
“…22 Three years later, diminazene (DIZE), 23 an agent already established in veterinary medicine, for example, as a treatment option against trypanosomiasis, 24 was identified via virtual screening as an ACE2 activator. In the following years, XNT and DIZE have been used successfully to treat a vast array of conditions, such as hypertension, 22,25 pulmonary hypertension, [26][27][28] cardiac and renal fibrosis, 22 and glaucoma, 29 in experimental rat or mice models. The premise of the therapeutic benefit has been attributed to ACE2 activation and the conversion of Ang II to Ang (1-7).…”
mentioning
confidence: 99%